Disinformation and manipulation in digital media : information pathologies - Culloty, Eileen; Suiter, Jane (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Drawing on research from multiple disciplines and international case studies, this book provides a comprehensive and up-to-date understanding of online disinformation and its potential countermeasures. Disinformation and Manipulation in Digital Media presents a model of the disinformation process which incorporates four cross-cutting dimensions or themes: bad actors, platforms, audiences, and countermeasures. The dynamics of each dimension are analysed alongside a diverse range of international cases studies drawn from different information domains including politics, health, and society. In elucidating the interrelationship between the four dimensions of online disinformation and their manifestation in different international contexts, the book demonstrates that online disinformation is a complex problem with multiple, overlapping causes and no easy solutions. The book's conclusion contextualises the problem of disinformation within broader social and political trends and discusses the relevance of radical innovations in democratic participation, education, and digital governance to counteract the post-truth environment. This up to date and thorough analysis of the disinformation landscape will be of interest to students and scholars in the fields of journalism, communications, politics and policy as well as policymakers, technologists and media practitioners"--
Introduction: Information Pathologies -- Bad Actors -- Platforms -- Audiences -- Countermeasures -- Conclusion: Post-Truth Communication.
OCLC-licensed vendor bibliographic record.
Keywords: Fake news -- Social aspects; Disinformation -- Social aspects; Propaganda -- Social aspects; Digital media -- Moral and ethical aspects; Internet -- Moral and ethical aspects; LANGUAGE ARTS & DISCIPLINES / Journalism